Can we increase male involvement in AIDS treatment? - Birungi, Josephine; Mills, Edward J. (My University, 2010)
In Uganda, men and boys are diffi cult to enrol in testing and treatment, and have increased mortality compared with women and girls. 5 Ad hoc HIV- positive men’s groups reach out to other men to increase testing and acceptance of results. However, in our experience, funders are unsupportive or unwilling to provide assistance to male-targeted interventions. Thus, male groups lack the sophistication of the female- focused eff orts and are unsustainable. Men, whether we blame them for their behaviours or not, represent a necessary population to engage with.
Keywords: Male involvement; HIV/AIDS; AIDS treatment